Cyclic behavior of braced concrete frames: Experimental investigation and numerical simulation - Hadad S. Hadad; Ibrahim M. Metwally; Sameh El-Betar (HBRC Journal, 2017)
RC shear walls have been widely used as the main lateral-load resisting system in medium and high-rise buildings because of their inherent large lateral stiffness and load resistance. But, in general, the energy dissipating capacity of RC shear walls is not very good and it is found that using the bracing system gives good results. The main purpose of this paper is to study the effect of the different types of bracing on the lateral load capacity of the frame. Also, the research contains a comparison between the braced and infilled frames to decide the best system. The research scheme consists of four frames; the bare frame, two frames one was braced with concrete, the second was braced with steel bracing and the fourth frame was infilled with solid cement bricks. All the specimens were tested under cyclic loading. The results gave some important conclusions as; braced and infilled the bare frames increased the lateral strength of the bare frame depending on the type of bracing and infill. Also, the different types of bracing and the infill increased the initial stiffness of the bare frame by a reasonable value. The energy dissipation for the braced and infilled frames is always higher than that for the bare frame up to failure. Also, numerical modeling was carried out with the nonlinear software platform (IDARC). The numerical results obtained with the calibrated nonlinear model are presented and compared with the experimental results. Good agreement was achieved between the numerical simulation and the test results.